Nguyen Dinh Chieu's concept of morality to be human: Nguyen Dinh Chieu's concept of morality to be human - Lai Quang (Perkumpulan Dosen Program Hibah Indonesia, 2023)
Nguyen Dinh Chieu is one of the typical thinkers in Vietnam in the second half of the 19th century. His works, not only are immortal pages praising the heroic fight of our people against the Western invaders from the first time they set foot in our country, but also express a philosophy human life, in which his concept of morality to be human has a profound, humanistic meaning. He is not only a shining example of the indomitable spirit of fighting against foreign invaders, of patriotism and love for the people, but also represents the noble spirit of humanity.